Integrated centralized treatment system and process for water-based waste and oil-based waste from oil drilling
Through the integrated centralized treatment system of water-based waste and oil-based waste of oil-based waste, combined with centralized treatment equipment and ceramic manufacturing process, the problems of low efficiency and environmental protection of drilling waste are solved, and efficient environmental protection treatment and resource recycling are achieved.
Patent Information
- Application Number
- CN202211684684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The environmental protection and efficient treatment of water-based waste and oil-based waste in oil drilling are difficult. The existing technology has problems such as large equipment footprint, chaotic management and low processing efficiency.
The integrated centralized treatment system for water-based waste and oil-based waste of oil drilling is adopted to reduce the amount of the dehydrated sludge and ash slag through rock chip collection and centralized treatment equipment (such as rubber breaking and destabilizing devices, plate and frame filter presses, rotary dryers, centrifuges, rotary kilns, etc.), and the dehydrated sludge and ash slag are obtained, and the ceramic granules are further produced through crushing and grinding, water addition, aging, molding and granulation, drying and sintering processes.
It realizes efficient environmentally friendly treatment of oil drilling waste, reduces the release of on-site environmentally friendly equipment, improves operating efficiency, avoids the harm of pollutants to the environment, and improves treatment efficiency through resource recycling.
Smart Images

Figure CN116003154B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil drilling cuttings and mud waste treatment, and in particular to an integrated centralized treatment system and process for oil drilling water-based waste and oil-based waste. Background Art
[0002] In the development and production of oil, in order to balance the formation pressure and maintain the collapse of the wellbore and well wall, drilling fluids with added composite materials such as bentonite, barite, high molecular chemical organic compounds, emulsifiers, etc. are often used. Along with the mining process, the use of drilling fluids will produce waste pollutants, including production wastewater or waste rock cuttings, etc. The pollutants often have high COD, high BOD, high salt, high ammonia nitrogen, excessive heavy metals, high molecular organic chemicals and other problems. These pollutants are carried to the ground through the drilling fluid. If they are not effectively treated, they will cause great harm to vegetation, water bodies, soil and human health.
[0003] With the continuous strengthening of environmental awareness in recent years, the current methods for treating waste pollutants are:
[0004] Cleaning work is carried out at the mining site, and the drilling fluid waste is collected and reduced. The process technology flow is a drilling fluid waste equipment receiving system composed of a screw conveyor and a liquid receiving tank. The water-based waste and oil-based waste are then reduced and separated into solid waste and liquid waste; then the water-based solid waste and oil-based solid waste are treated separately.
[0005] The above treatment of mining drilling waste has the following problems:
[0006] a. In order to explore the reserves during oil drilling, a large number of drilling rigs and equipment are deployed together with environmental protection equipment at the mining site, which takes up a lot of space and easily leads to management chaos. In addition, the drilling and mining work is highly mobile. In order to ensure environmental protection requirements, environmental protection equipment and sewage storage tanks will be moved with the site transfer, which brings great difficulties to the environmental protection and technical requirements of sewage storage tanks. Especially in the rainy season, pollutants are easily soaked in rainwater, leaching organic salts, polymer compounds, mineral oils and other toxic substances into rivers or fields, changing the ecological environment and soil properties, and causing water pollution or the problem of farmland being uncultivable.
[0007] b. For the sludge generated after the reduction of discarded water-based waste, choose local brick factories to make bricks for use. However, the amount of water-based solid waste added to brick making cannot be greater than 10% of the clay ratio. If the solid waste is greater than 10%, the fired red bricks are prone to cracking, deformation and other unqualified products. Since the amount added is too small, the solid waste removal rate is very low, resulting in a large amount of water-based solid waste pollutants piling up in the brick factory, and it is impossible to form an efficient treatment method.
[0008] c. After the reduction and incineration pyrolysis of discarded oil-based waste, the remaining ash is currently treated by adding 15% to the cement plant for reuse, or directly stacking it, which is also unable to form an efficient treatment method.
[0009] How to achieve environmentally friendly and efficient treatment of water-based waste and oil-based waste in oil drilling operations is a problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0010] The purpose of the present invention is to provide an integrated centralized treatment system and process for water-based waste and oil-based waste in oil drilling, and the purpose is to treat water-based and oil-based waste in oil drilling efficiently and environmentally friendly through a centralized system and process method. To achieve the above-mentioned purpose of the invention, the technical solution of the present invention is as follows:
[0011] The integrated centralized treatment system for water-based waste and oil-based waste from oil drilling includes using rock cuttings collection equipment to collect water-based waste and oil-based waste respectively, transporting the collected waste to corresponding sewage storage tanks by means of transportation equipment, reducing the waste by means of centralized treatment equipment, using equipment including degumming and destabilizing device, plate and frame filter press, and drying device, the equipment is used to degumming and destabilizing, dehydrating, and drying the drilling water-based waste to a moisture content of 30% to obtain dehydrated sludge; reducing the oil-based waste by means of centralized treatment equipment, using equipment including spin dryers and centrifuges, mainly used to perform solid-liquid separation on the oil-based waste to obtain deoiled oil-based sludge, then heating the pollutants, and incinerating and pyrolyzing the deoiled oil-based waste by means of rotary kiln heating and pyrolysis to produce ash with a moisture content of 0 and an oil content of 1-4%; calcining the ceramsite embryo to obtain ceramsite; the equipment of the ceramsite manufacturing unit includes a crusher, a pulverizer, a mixer, an extruder, a heating device, and a sintering equipment.
[0012] The integrated centralized treatment process for oil drilling water-based waste and oil-based waste includes the following steps:
[0013] Step 1, dewatering the drilling water-based waste until the water content is 30% to obtain dewatered sludge, and the plasticity value of the dewatered sludge is greater than 12;
[0014] Step 2, dehydrating and deoiling the drilling oil-based waste until the oil content is 1-4%;
[0015] Step 3, heating and incinerating the oil-based sludge obtained in step 2 to obtain ash, wherein the ash plasticity value is less than 12;
[0016] Step 4: Evenly mix the dewatered sludge in step 1 and / or the ash in step 3, crush them and granulate them to obtain ceramsite embryos; and calcine the ceramsite embryos to obtain ceramsite.
[0017] Among them, in step 1, the water-based waste is dehydrated, and the wastewater produced by the gel breaking and destabilization device and the plate and frame filter press is discharged to the sewage treatment plant.
[0018] In step 2, the oil-based waste is dehydrated and deoiled, and the waste liquid produced by the dryer and the centrifuge can be recycled for use in oil-based drilling operations after passing through a purification process.
[0019] In the calcination and granulation process in step 4, the tail gas generated during the calcination process can also be treated by using a secondary combustion chamber, a dust removal device, a desulfurization device, an activated carbon adsorption device, etc. to ensure that the production process is environmentally friendly.
[0020] The dewatered sludge after the reduction treatment is mixed with the ash and stirred to produce ceramsite in the following way:
[0021] (1) Crushing and grinding: Dewatered sludge and ash are mixed in a mass ratio of 7:3, and then crushed. The sludge powder is crushed by a crusher, and then ground by a grinder to make the particle size of the sludge powder 0.2-1mm;
[0022] (2) Add water for aging: Mix the mud powder in (1) with water in a mass ratio of 3.5-5:1, use a mixer to fully mix and knead the mud blocks into rectangular or cylindrical shapes, cover the surface of the mud blocks with a film to retain moisture, and let the mud blocks stand for 8-12 hours;
[0023] (3) Molding and granulation: put the slurry block in (2) into an extruder, extrude strips with a diameter of 10 mm, and cut and granulate them according to a length of about 10-15 mm to form a cylindrical or spherical shape;
[0024] (4) Drying: Place the crucible containing the ceramsite body in (3) into a constant temperature drying oven, set the drying temperature to 100-105°C, and the drying time to 2-8 hours to remove moisture, so that the moisture content of the ceramsite body is 0.9%-1.5%;
[0025] (5) Sintering: The dried ceramsite body is sintered in a high temperature furnace at a temperature of 950-1070°C for 0.5 h. After being taken out and naturally cooled, the ceramsite is obtained.
[0026] Furthermore, in the crushing and grinding process, the particle size of the mud powder is 0.5 mm, and a pore-forming agent is added to the mud powder; wherein the pore-forming agent is at least one of sodium bicarbonate, iron oxide, and calcium carbonate, and the mass ratio of the pore-forming agent to the mud powder is 1-10:100.
[0027] Furthermore, in the drying process, the drying time is set to 6-8 hours, and the moisture content of the ceramsite body is controlled to be 1%-1.05%. Furthermore, in the sintering process, the firing temperature is set to 1000-1050°C.
[0028] Furthermore, a pre-firing process can be added after the drying step and before the sintering step, and the ceramsite body is placed in a pre-firing furnace with a firing temperature of 200-500° C. and a firing time of 0.5 h.
[0029] The content and manufacturing method of ash: the ash is fired in a rotary kiln, and an insulating material is set on the outer layer of the rotary kiln. The kiln body is installed with a slope ratio of 1:10, and the temperature in the kiln is set at 500°C. After directly burning the oil-based rock cuttings sludge, the ash is obtained; wherein, the water content is 0, the oil content is 1-4%, and the main components of the ash are silicon dioxide and magnesium ions.
[0030] Furthermore, a spiral mixing propeller is welded on the inner wall of the rotary kiln, so that the oil-based sludge can be transmitted on the rotary kiln transmission line, which facilitates the combustion and pyrolysis of the oil-based sludge to obtain ash.
[0031] The beneficial effects of the present invention are as follows: by means of an integrated centralized treatment system, the on-site environment of oil drilling is reduced by the deployment of environmental protection equipment, so that the drilling operation area is increased, and the implementation of on-site operations is convenient; when on-site operations are mobile, the time and capital investment for dismantling and installing environmental protection equipment are reduced, and the impact of on-site drilling production on environmental protection issues is avoided, thereby improving the timeliness of on-site operations; by establishing a centralized treatment site in an area outside the site, the drilling cuttings and sludge pollutants can be effectively controlled within a fixed range, and when rainy and snowy weather occurs, the drilling cuttings pollutants will not "run, emit, or leak" at the drilling site, thereby improving the on-site cleanliness management and avoiding the possible pollution of soil, rivers, farmland, and the like by pollutants.
[0032] Through the centralized treatment of drilling water-based and oil-based wastes, the dehydrated sludge and ash obtained after treatment are made into expanded clay. Expanded clay is generally made of clay. The method of making expanded clay from waste solids can also produce expanded clay with high strength and light weight without using clay while protecting the ecological balance. This allows drilling cuttings pollutants to be recycled, achieve resource regeneration, and improve production utilization.
[0033] Dewatered sludge with a plasticity value of >12 and ash with a plasticity value of <12 have a good compatibility granulation effect. After being mixed and granulated, the prepared ceramsite is tested. From the physical property test of the ceramsite, it can be seen that the water absorption rate of the ceramsite is 12%, the bulk density is less than 800 kg / m³, and the cylinder pressure strength is 4.1MPa, which meets the water absorption rate, bulk density and strength requirements of ceramsite products; through the treatment of drilling waste solids, waste can be turned into treasure and resource utilization can be effectively realized.
[0034] By integrating dewatered sludge and ash into expanded clay, all drilling waste solids can be effectively utilized, solving the problem of existing technologies that only add 10% or 15% to treat them, providing a quantitative solution for pollutants and greatly improving the treatment efficiency of drilling waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] FIG1 is a system structure diagram of Embodiment 1 of the present invention;
[0036] FIG2 is a water-adding aging step for preparing ceramsite in Example 1 of the present invention;
[0037] FIG3 is a granulation step of preparing ceramsite in Example 1 of the present invention;
[0038] FIG4 is a drying step for preparing ceramsite in Example 1 of the present invention;
[0039] FIG5 is a sintering step of ceramsite manufacturing in Example 1 of the present invention;
[0040] FIG6 is a picture of the ceramsite in Example 7 of the present invention after being pre-calcined at 350° C. after drying;
[0041] FIG. 7 is a picture of the ceramsite in Example 7 of the present invention after being pre-calcined at 500° C. after drying. DETAILED DESCRIPTION
[0042] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. Example 1
[0043] During the drilling and production process of the Inner Mongolia Oilfield, a 40-meter U300 screw conveyor was used at the drilling site to transport water-based waste and oil-based waste to 36 cubic meter open solid-liquid sedimentation tanks respectively. After initial sedimentation, they were respectively sent to storage tanks, and then the waste was sent to closed tank trucks by conveying pumps. The rock cuttings and mud pollutants were sent to the integrated rock cuttings and mud treatment center established outside the mining site.
[0044] A closed and fixed sewage storage tank is established in the integrated treatment center, and water-based waste is discharged into the water-based sewage storage tank. A degelling and destabilizing device and a plate and frame filter press are used to centrally treat the pollutants. The degelling and destabilizing device and the plate and frame filter press are used to dehydrate the drilling water-based waste, separate the mud and water to a water content of 60%, and then dry it to a water content of about 30% to obtain dehydrated sludge. The wastewater generated in the process of water-based waste treatment can be directly discharged to the sewage treatment plant.
[0045] Oil-based waste is discharged into the oil-based waste storage tank. The oil-based waste is separated into solid and liquid by a spin dryer and a centrifuge to obtain de-oiled oil-based waste. The de-oiled oil-based waste is then incinerated and pyrolyzed by heating and pyrolysis in a rotary kiln to produce ash. The ash plasticity value is 0, the water content is 0, and the oil content is 2%. After testing, it is found that the main components of the ash are silicon dioxide and magnesium ions. Among them, the waste liquid generated in the process of oil-based waste treatment can be used in drilling operations after recycling and purification. The dehydrated sludge and ash are crushed and mixed in a mass ratio of 7:3, and then stirred evenly to manufacture ceramsite; the ceramsite manufacturing unit equipment includes a crusher, a pulverizer, a mixer, an extruder, a heating device and a sintering equipment; among them, the pulverizer uses a ball mill, the heating device uses a drying box, and the sintering equipment is a high-temperature furnace.
[0046] By discharging wastewater from drilling waste into a water treatment plant, the waste solids are made into expanded clay, thus turning waste into treasure and recycling resources.
[0047] Before treatment, the Inner Mongolia water-based waste was sent to the Physical and Chemical Testing Institute of China Cement Development Center for chemical and industrial analysis. The results are as follows:
[0048] Table 1 Chemical analysis of water-based mud in Inner Mongolia (unit %)
[0049]
[0050] Table 2 Analysis of Inner Mongolia water-based mud industry (unit %)
[0051]
[0052] From the results of chemical analysis, it can be seen that the chemical composition of water-based mud is a variety of metals, which is similar to clay minerals. From the results of industrial analysis, it can be seen that the ash content of water-based mud is as high as 81.83%, while the volatile matter is 11.94%, and the air-dried basis moisture is 2.3%; there is a certain amount of organic matter, which meets the requirements of ceramsite firing composition.
[0053] The production of ceramsite is carried out in the following ways:
[0054] 1. Crushing and grinding: Mix the dewatered sludge and ash in a mass ratio of 7:3, use a jaw crusher to further crush them, and then use a ball mill to grind the broken pieces to control the particle size of the sludge powder to less than 200μm.
[0055] 2. Add water for aging: Mix the mud powder and water in a mass ratio of 5:1, use a mixer to fully mix and knead, and then process it into a rectangular shape. Put the mud block in a tray, cover it with a film to keep its moisture, and let it age for 12 hours.
[0056] 3. Molding and granulation: put the mud block into the extruder, extrude the strips with a diameter of 10mm, and cut them into strips with a length of about 15mm.
[0057] Cut into short strips.
[0058] 4. Drying: The crucible containing the ceramsite body in step 3 is placed in a constant temperature drying oven at 105°C for 8 hours to remove moisture and make the moisture content of the ceramsite body 1.0%;
[0059] 5. Sintering: The dried ceramsite body is sintered in a high temperature furnace at a firing temperature of 1050°C for 300 minutes. After being taken out, it is naturally cooled to obtain ceramsite.
[0060] The ceramsite was sent to the 21st Tianjin Quality Supervision and Inspection Station for testing of heavy metal content and organic matter. The test results are shown in the following table:
[0061] Table 3 Comparison of heavy metals in oil drilling waste and its fired ceramsite
[0062]
[0063] It can be seen from the above table that the contents of barium, total chromium, nickel and lead in oil drilling waste all exceed the relevant national standards. After sintering into expanded clay, the metal leaching values were measured: the detection value of barium was 0.02 mg / L, far below the national standard value of 100 mg / L; the detection value of total chromium was <0.01 mg / L, far below the national standard value of 1 mg / L; the detection value of nickel was 0.05 mg / L, far below the national standard value of 5 mg / L; the detection value of lead was <0.01 mg / L, far below the national standard value of 5 mg / L; the detection value of hexavalent chromium was <0.004 mg / L, far below the national standard value of 5 mg / L, and so on; and the organic matter was almost burned during the high-temperature firing process.
[0064] Table 4 Physical properties test table of ceramsite
[0065]
[0066] As a lightweight aggregate, ceramsite has a bulk density of less than 1100 kg / m 3 The density of concrete made with ceramsite as aggregate is 1100~1800kg / m 3, the corresponding concrete compressive strength is 30.5~40.0Mpa; and as can be seen from the above table, the ceramsite made from oil drilling water-based waste and oil-based waste has a water absorption rate of 12%, a bulk density of less than 800 kg / m³, and a cylinder pressure strength of 4.1MPa; it fully meets the data requirements for water absorption rate, bulk density and strength of ceramsite products; it realizes the harmless treatment of oil drilling water-based waste and oil-based waste, and also realizes the transformation of waste into treasure and resource recycling. Example 2
[0067] During the drilling and production process of Tianjin Dagang Oilfield, rock cuttings collection equipment is used to collect water-based waste, which is then transported to a centralized environmental protection treatment center outside the drilling site by transport vehicles. The waste is dumped into the water-based sewage storage tank of the centralized environmental protection treatment center, and centralized treatment equipment is used to reduce the amount of water-based waste. After the reduction treatment, the pollutants are separated into wastewater and solid waste, and the wastewater is transported to a wastewater treatment plant for harmless treatment. The waste is dewatered sludge.
[0068] The dewatered sludge is fully stirred to produce expanded clay. The equipment of the expanded clay production unit includes a crusher, a grinder, a mixer, an extruder, a heating device and a sintering device.
[0069] The ceramsite manufacturing method comprises the following steps:
[0070] 1. Crushing and grinding: First, the dewatered sludge is crushed by a jaw crusher. The crushed small pieces are put into a mortar and ground with a grinder. After grinding into powder, they are sieved with a 200μm sieve.
[0071] 2. Add water for aging and forming granules: Mix the mud powder in the above step with water in a mass ratio of 3.5:1, then stir, use a mixer to fully mix and knead, process into a rectangular shape, put the mud block into a tray, and cover it with a film to keep its moisture. After static aging for 12 hours, put it into the extruder and extrude granules into spheres with a diameter of 10mm.
[0072] 3. Low temperature drying: Place the crucible containing the slurry ceramsite body into a constant temperature drying oven at 105°C and dry for 6 hours to remove moisture, so that the moisture content of the ceramsite body is 1.5%.
[0073] 4. Pre-sintering of the green body: Place the dried ceramsite green body into a high temperature furnace and pre-sinter at 500°C for 0.5h.
[0074] 5. High temperature sintering: put the pre-fired ceramsite into a high temperature furnace at 1070°C for 30 minutes to form ceramsite. After taking it out, cool it naturally in the room to obtain ceramsite. Example 3
[0075] The water-based waste obtained from drilling in the Dagang Oilfield in Tianjin was collected in the same manner as in Example 2, and the waste was used to make ceramsite, which was different from Example 2: the dehydrated sludge was crushed, ground into powder, and then sieved with a 200 μm sieve. After granulation, it was dried in a constant temperature drying oven at 105°C for 2h, pre-calcined at 500°C for 30min, and then calcined at 1000°C for 30min. Example 4
[0076] The water-based waste obtained from drilling in the Dagang Oilfield in Tianjin was collected in the same manner as in Example 2, and the waste was used to make ceramsite, which was different from Example 2: the dehydrated sludge was crushed, ground into powder, and then sieved with a 200 μm sieve. After granulation, it was dried in a constant temperature drying oven at 105°C for 2h, pre-calcined at 350°C for 30min, and then calcined at 1000°C for 30min. Example 5
[0077] The water-based waste obtained from drilling in the Dagang Oilfield in Tianjin was collected in the same manner as in Example 2, and the waste was used to make ceramsite, which was different from Example 2: the dehydrated sludge was crushed, ground into powder, and then sieved with a 200 μm sieve. After granulation, it was dried in a constant temperature drying oven at 105°C for 2h, pre-calcined at 200°C for 30min, and then calcined at 1000°C for 30min. Example 6
[0078] The water-based waste obtained from drilling in the Dagang Oilfield in Tianjin was collected in the same manner as in Example 2, and the waste was used to make ceramsite, which was different from Example 2: the dehydrated sludge was crushed, ground into powder, and then sieved with a 1 mm sieve. After granulation, it was dried in a constant temperature drying oven at 105°C for 8h, pre-calcined at 500°C for 30min, and then calcined at 1000°C for 30min.
[0079] In the firing process of the ceramsite in Examples 3-5, it was found that when the drying time was set to 2h and the pre-burning was set to 200℃, 350℃, and 500℃ respectively, the ceramsites all burst a few minutes after the pre-burning started, and the number of bursts accounted for more than half of the total number. One ceramsite generally burst into several parts, and the bursting sound was very loud. The number of ceramsites prepared in the experiment was unstable; while the ceramsites in Examples 2 and 6, when the drying time reached 6-8h, no matter whether it was 200μm or 1mm granulated ceramsite, would not burst when pre-burned at a higher temperature of 500℃; the moisture content of the ceramsite prepared in Examples 3-5 was tested, and it was found that the moisture content of the ceramsite prepared in Examples 3-5 was 3.7%, and the moisture content of the ceramsite prepared in Examples 2 and 6 with a drying time of 6-8h was only 1.05%, which also showed that the high moisture content caused the ceramsite to burst, so the cause of the pre-burning bursting phenomenon was the drying time. When the granulated sludge was dried for 6-8h, the moisture content of the ceramsite was only 1.05%, which also showed that the high moisture content caused the ceramsite to burst. Therefore, the cause of the pre-burning bursting phenomenon was the drying time. The amount of expanded clay produced is stable and will not explode. Example 7
[0080] The water-based waste obtained from drilling and production in the Dagang Oilfield in Tianjin is collected in the same manner as in Example 2, and the waste is used to manufacture ceramsite, which is different from Example 2: the dehydrated sludge and ash are mixed in a mass ratio of 7:3, and a jaw crusher is used to further crush the sludge, and the crushed small pieces are then ground in a ball mill to make the particle size of the mud powder 0.5 mm, and a certain proportion of pore formers are mixed in the mud powder, wherein the pore formers are calcium carbonate, sodium bicarbonate and iron oxide; after adding different proportions of pore formers to the mud powder, it is mixed with water to form spherical ceramsite, and the following table is a component table of different proportions and pore formers:
[0081] Table 5 Pore-forming agent composition table
[0082]
[0083] The particle density and water absorption rate of the above 6 samples were tested; according to the test requirements of ceramsite, the bulk density, particle density, water absorption rate and cylinder pressure strength of the ceramsite were tested. The experimental test data were particle density and 1h water absorption rate, which were calculated using the following method:
[0084]
[0085]
[0086] The test method for the volume of expanded clay is as follows: soak the expanded clay in water for 1 hour, remove the moisture on the surface of the particles with a towel, and then put the expanded clay into a measuring cup filled with water to measure the volume.
[0087] Then the above 6 samples were put into water for water absorption test. It was found that the surface of each group of samples was covered with a layer of tiny bubbles. Among them, the bubbles in sample 3 were the largest, and the bubbles in samples 4, 5 and 6 were very small. The size of the bubbles reflected the size of the surface pores.
[0088] Then the crucible containing the above 6 samples of ceramsite bodies was placed in a constant temperature drying oven at 105℃, dried for 6 hours, and the moisture was removed to make the ceramsite body have a moisture content of 1.05%. After drying, the ceramsite body was pre-fired, and the temperature was set to 350℃ and 500℃ respectively; then the ceramsite bodies pre-fired at different temperatures were fired at 950℃ or 1000℃, and the ceramsite products were obtained after cooling; it was found from the pre-fired at different temperatures that the surface of the particles after pre-fired at 350℃ was basically black, indicating that a large amount of organic matter was volatilized and decomposed at this temperature, but not completely burned; after pre-fired at 500℃, the surface of the particles was found to be gray, indicating that most of the organic matter in the sludge was completely burned. From the color point of view, sample 1 and sample 3 were fired at 950℃ and 1000℃, sample 1 was earthy yellow, sample 3 was yellowish brown, and other samples were basically brick red or reddish brown.
[0089] The data of the experimental test after the ceramsite is made are as follows:
[0090] Table 6 Test data after firing at 950℃
[0091]
[0092] Table 7 Test data after firing at 1000℃
[0093]
[0094] From the two firing temperatures, the water absorption rate of sample 3 with sodium bicarbonate added is basically the highest, which indicates that the addition of sodium bicarbonate
[0095] Sodium hydrogen is not conducive to controlling the water absorption rate of the product. In the water absorption experiment, it was found that the surface bubbles of sample 3 were the largest.
[0096] The water absorption rate of sample 4 of iron oxide is low at both firing temperatures, but the particle density is not low. It can also be seen from sample 4 that the surface is very dense, indicating that iron oxide promotes the formation of the firing liquid phase.
[0097] Thus, it can be seen that in the ceramsite manufacturing method of Example 7, calcium carbonate or iron oxide porogen is added to the mud powder in an amount of 8%, which is most conducive to forming pores and reducing the particle density; after the mud powder and water are mixed and granulated, the ceramsite body is placed in a dryer at 105°C for a drying time of not less than 6 to 8 hours, and the moisture content of the body after drying is controlled to be about 1%. After drying, it is pre-fired at 500°C, and the pre-fired ceramsite body is sintered at a high temperature of 1000°C. After cooling, a ceramsite product having bulk density, particle density, water absorption rate and cylinder compressive strength that meet the requirements can be obtained.
[0098] The embodiments described above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications and equivalent substitutions made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An integrated centralized treatment system for water-based waste and oil-based waste from oil drilling, comprising using rock cuttings collection equipment to collect water-based waste and oil-based waste respectively, using transportation equipment to transport the collected waste to corresponding waste storage tanks respectively, and using centralized treatment equipment to reduce the waste; the characteristics are: It consists of three equipment units: The first equipment unit is a water-based waste mud-water separation treatment unit; the equipment includes a gel-breaking and destabilizing device, a plate-frame filter press, and a drying device, and the drilling water-based waste is destabilized, dehydrated, and dried to a moisture content of 30% to obtain dehydrated sludge; The second equipment unit is an oil-based waste de-oiling slag processing unit; the equipment used includes a spin dryer, a centrifuge, and a rotary kiln, wherein the spin dryer and the centrifuge perform solid-liquid separation on the oil-based waste to obtain de-oiled oil-based sludge; and the rotary kiln is used to heat and pyrolyze to produce ash slag; The third equipment unit is the ceramsite manufacturing unit; the equipment used includes a crusher, a grinder, a mixer, an extruder, a heating device and a sintering device; The specific steps include: Step 1, dehydrating the drilling water-based waste until the water content is 30% to obtain dehydrated sludge; Step 2, dehydrating and deoiling the drilling oil-based waste until the oil content is 1-4%; Step 3, heating and incinerating the oil-based sludge obtained in step 2 to obtain ash residue; the main components of the ash residue are silicon dioxide and magnesium ions; Step 4, mixing the dehydrated sludge in step 1 and the ash in step 3, crushing and granulating to obtain a ceramsite embryo; calcining the ceramsite embryo to obtain ceramsite; Wherein, in step 4, the ceramsite manufacturing method further comprises the following steps: (1) Crushing and grinding: Dewatered sludge and ash are mixed in a mass ratio of 7:3, and then crushed. The sludge powder is crushed by a crusher, and then ground by a grinding mill to make the particle size of the sludge powder be 0.2-1 mm; the particle size of the sludge powder is 0.5 mm, and a pore-forming agent is added to the sludge powder; wherein the pore-forming agent is calcium carbonate, and the mass ratio of the pore-forming agent to the sludge powder is 8:100; (2) Aging with water: The mud powder in (1) is mixed with water in a mass ratio of 3.5-5:1, and the mud blocks are fully mixed and kneaded using a mixer to form rectangular or cylindrical shapes, and the surface of the mud blocks is coated with a film to retain moisture, and the mud blocks are aged for 8-12 hours; (3) Forming and granulation: the slurry block in (2) is placed into an extruder, extruded into strips with a diameter of 10 mm, and cut and granulated into cylindrical or spherical shapes according to a length of 10-15 mm; (4) Drying: placing the crucible containing the ceramsite body in (3) into a constant temperature drying oven, setting the drying temperature to 100-105° C., the drying time to 6-8 h, and removing moisture to make the moisture content of the ceramsite body to be 1-1.05%; (5) Sintering: The dried ceramsite body is sintered in a high temperature furnace at a temperature of 1000° C. for 0.5 h, and then taken out and naturally cooled to obtain ceramsite; A pre-firing step is also provided after the drying step and before the sintering step, wherein the ceramsite green body in the drying step (4) is placed in a pre-firing furnace, the firing temperature is 500° C., and the firing time is 0.5 h; In step 4, the water-based waste and oil-based waste from oil drilling are processed to prepare ceramsite, wherein the water absorption rate of the ceramsite is 12% and the bulk density is less than 800 kg / m 3 , the cylinder pressure strength is 4.1MPa.
2. The integrated centralized treatment system for oil drilling water-based waste and oil-based waste according to claim 1 is characterized by: A spiral mixing propeller is welded on the inner wall of the rotary kiln to transmit the oil-based sludge on the rotary kiln transmission line, thereby facilitating the combustion and pyrolysis of the oil-based sludge.
3. The integrated centralized treatment process for oil drilling water-based waste and oil-based waste according to claim 1 is characterized by: Step 3 adopts rotary kiln firing, sets insulation material on the outer layer of rotary kiln, sets the temperature in kiln to 500°C, directly burns oil-based sludge to obtain ash.
Citation Information
Patent Citations
Ceramsite and preparation method thereof
CN112341238A
System for preparing fracturing propping agent from oil-based drilling cuttings
CN210738502U
Integrated centralized treatment system for water-based waste and oil-based waste in petroleum drilling
CN219093106U